2018
DOI: 10.1186/s12884-018-1720-6
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal birth after caesarean versus elective repeat caesarean delivery after one previous caesarean section: a cost-effectiveness analysis in four European countries

Abstract: BackgroundThe OptiBIRTH study incorporates a multicentre cluster randomised trial in 15 hospital sites across three European countries. The trial was designed to test a complex intervention aimed at improving vaginal birth after caesarean section (VBAC) rates through increasing women’s involvement in their care. Prior to developing a robust standardised model to conduct the health economic analysis, an analysis of a hypothetical cohort was performed to estimate the costs and health effects of VBAC compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 44 publications
0
25
1
2
Order By: Relevance
“…When described, it was set at US$50,000 (9), US$100,000 (2), US$50,000‐100,000 (2), UK£20,000 (€22,753) (2) and €45,000 (2), equivalent to US$32,000 and US$63,000 at the time of publication. One study that considered four European countries, described country‐specific thresholds that were equivalent to three countries’ gross domestic product (37,719 € for Germany, €36,633 for Belgium and €27,219 for Italy) while that for Ireland was set at €45,000 …”
Section: Resultsmentioning
confidence: 99%
“…When described, it was set at US$50,000 (9), US$100,000 (2), US$50,000‐100,000 (2), UK£20,000 (€22,753) (2) and €45,000 (2), equivalent to US$32,000 and US$63,000 at the time of publication. One study that considered four European countries, described country‐specific thresholds that were equivalent to three countries’ gross domestic product (37,719 € for Germany, €36,633 for Belgium and €27,219 for Italy) while that for Ireland was set at €45,000 …”
Section: Resultsmentioning
confidence: 99%
“…Other neonatal outcomes examined (admission to NICU, and preterm birth) also did not differ significantly between the two groups. Separate economic analysis showed that VBAC resulted in a cost reduction ranging from €3,334,052 (Germany) to €66,162,379 (Ireland) and gains in quality-adjusted life-years from 6399 (Italy) to 7561 (Germany) per 100,000 women birthing in each country [37]. Limitations of the OptiBIRTH cluster trial include missing data from 46 of the 2002 recruited women who moved away, or gave birth in another maternity unit (2.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Looking at these hypothetical cohort studies, two European studies were conducted comparing attempting a VBAC with ERCS . VBAC was found to be a dominant strategy in four EU countries (Belgium, Germany, Ireland, and Italy), resulting in a cost and utility gain, over ERCS using a 6‐week and lifetime time horizon.…”
Section: Discussionmentioning
confidence: 99%
“…A decision tree has been developed in the context of OptiBIRTH (Figure ) . The algorithm of the decision tree was similar for all three countries and consisted of two main arms: intervention and control.…”
Section: Methodsmentioning
confidence: 99%